Biomolecular characterization of Fusarium poae strains isolated from durum wheat in central Italy. - Alberti, I.; Prà, Dal M.; Tonti, S.; Montanari, M.; Prodi, A.; Pancaldi, D. (Plant Breeding and Seed Science, 2011)
Fusarium Head Blight (FHB) is a worldwide disease affecting wheat, barley and other grains, reducing kernel weight and grain yield; infected seeds may contain a large number of mycotoxins, including trichothe- cenes of type A and B. These compounds have already been associated with human and animal toxicoses. Most common species causing the disease are F. graminearum, F. culmorum and F. avenaceum, but in the last few years a gradual increase in incidence of another species, F. poae, has been reported. In general terms, F. poae is a relatively weak pathogen, but its contribute to the increase of mycotoxins level still has to be clarified. Durum wheat is widely cultivated in the central part of Italy, however the effective incidence of F. poae in this area still has to be investigated. In order to monitor Fusarium risk, we collected dozens of F. poae strains on seeds and glumes of durum wheat coming from some of the most important cultivated areas of Central Italy. Every isolate was identified both by microscope observation and by PCR assay with the primer pair Fp82 F/R. Strains were therefore subjected to a more accurate molecular characterization by Translation Elongation Factor 1-alpha (TEF-1α) gene sequencing.